Pengaruh Penerapan E-filing, Pemahaman Perpajakan, dan Kesadaran Wajib Pajak terhadap Kepatuhan Wajib Pajak Badan di KPP Pratama Malang Selatan - Agustinus Christian Wibsono (Jurnal Ilmiah Mahasiswa FEB, 2019)
The purpose of this study is to determine the effect of e-filing implementation, tax knowledge,and taxpayer awareness on corporate taxpayer compliance in KPP Pratama (Tax office) of South Malang, based on Theory of Reasoned Action (TRA) developed by Fishbein (1980) and Theory of Acceptance Model (TAM) developed by Davis in 1989. This study utilizes a survey to obtain the data, where the respondents of this study are 107 corporate taxpayers registered in KPP Pratama of South Malang. The results indicate that the e-filing implementation, tax knowledge, and taxpayer awareness have significant effect on the corporate taxpayer compliance.Keywords: Theory of Reasoned Action (TRA), Theory of Acceptance Model (TAM), Efiling Implementation, Tax Knowledge, Taxpayer Awareness, Corporate Taxpayer Compliance